Performance of the nanobio-based reagent for visualising wet fingerprints exposed to different levels of water salinity / Chao Wen Ting ... [et al.] - Chao, Wen Ting; Mahat, Naji Arafat; Azman, Aida Rasyidah; Muda, Nor Wajihan; Anuar, Nurazira (Faculty of Medicine, Universiti Teknologi MARA, 2021)
Introduction: Recovery of evidence such as murder weapons in waterways has been commonly reported. However, visualising latent fingerprints on the immersed substrates may prove challenging due to its obliteration by physicochemical parameters (e.g. pH, temperature, salinity) as well as the mechanical effect of water. Although the use of Small Particle Reagent (SPR) for visualising latent fingerprints on wet non-porous substrates has been suggested, it contains molybdenum and titanium that are toxic, and their utilisation must be reduced. Furthermore, no study verifies the chemical and/or physical interaction between SPR and the lipid constituents of wet latent fingerprints that leads to the visualisation of ridge details. Methods: The SPR and newly developed nanobio based reagent (NBR) i.e. Candida rugosa lipase-multiwalled carbon nanotubes (CRL-MWCNTs) were used for visualising latent fingerprints on glass slides immersed in water with salinity levels representing those of estuary and swimming pool for up to 15 days. Results: It was observed that the quality of the visualised fingerprints using NBR was comparable with that of SPR. Characterisations via instrument and bioinformatics analyses have also verified the incorporation of CRL onto MWCNTs and the chemical interaction between NBR and lipid constituents of wet latent fingerprints. Conclusions: Therefore, the newly developed NBR may prove a promising relatively greener alternative for substituting SPR for visualising latent fingerprints on glass slides immersed in different levels of water salinity.